Inter- and intrahemispheric sources of vestibular signals to V1 - Guy Bouvier; Alessandro Sanzeni; Elizabeth Hamada; Nicolas Brunel; Massimo Scanziani (Proceedings of the National Academy of Sciences, 2025)
Head movements are sensed by the vestibular organs. Unlike classical senses, signals from vestibular organs are not selectively conveyed to a dedicated cortical area but are broadcast throughout the cortex. This distributed processing pattern reflects the fundamental role of vestibular information in contextual modulation across diverse cortical computations. Surprisingly, the routes taken by vestibular signals to reach the cortex are still largely uncharted. Here, we show that the primary visual cortex (V1) receives real-time head movement signals—direction, velocity, and acceleration—from the ipsilateral pulvinar and contralateral visual cortex (VC). The ipsilateral pulvinar provides the main head movement signal, with a bias toward contraversive movements (e.g., clockwise movements in left V1). Conversely, the contralateral VC provides head movement signals during ipsiversive movements. Crucially, head movement variables encoded in V1 are already encoded in the pulvinar, suggesting that those variables are computed subcortically. Thus, the convergence of inter- and intrahemispheric signals endows V1 with a rich representation of the animal’s head movements.